@jvatsim
ok so x1 = 3*x2 is the next problem
so that means (3,1)^T (6,2)^T etc so nonempty
here x1=3*x2
the next step alphaX so x = (3x2, x2)^T so alpha *x
means (alpha*3*x2, alphax2)^T
and that equals alpha*3*x2 = alpha *x2
equals alpha(3*x2 = x2) so it passes and on to step 3
x + y
so here so i say x = (3x2,x2)^t
y = (3y2, y2)^t
we can still say 3x2+3y2 is = x2 + y2 ?? i think im missing something on this las step

Hey! We 've verified this expert answer for you, click below to unlock the details :)

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

@jtvatsim

i misspelled your name above, sorry

No problems. I'll be right back.

Looking for something else?

Not the answer you are looking for? Search for more explanations.

## More answers

Looking for something else?

Not the answer you are looking for? Search for more explanations.